BUMDes Development Program by Creating Packaging Design and Marketing Through Online Stores to Increase Economic Value in Balongmojo Village, Mojokerto - Widagdo, Reza Sarwo; Ardianik, Ardianik; Hartayu, Ratna; Setyadjit, Kukuh; Kusmiyati, Kusmiyati (Pelita: Jurnal Pengabdian kepada Masyarakat, 2024)
Achieving social welfare in all aspects is one of Indonesia's national goals. The village, as the smallest unit in the structure of society, is often neglected in efforts to achieve this goal. Therefore, regulations were created to address village issues in the hope of improving their welfare. One of the aspects regulated in village regulations is BUMDes, an entity that has a significant role in improving the village economy. This article will discuss the role of BUMDes in advancing the economy, with a case study of Balongmojo Village. Several work programs are proposed, including diversifying the production of kerupuk kelor, creating attractive packaging designs using Canva, and utilizing sugarcane bagasse waste to make it marketable. The results show that BUMDes can be effective in improving the economy of Balongmojo Village by developing local entrepreneurs through strong branding strategies and product market expansion.